The H-ARS Dose Response Relationship (DRR). Issue 5 (November 2015) - Plett, P. Artur; Sampson, Carol H.; Chua, Hui Lin; Jackson, William; Vemula, Sasidhar; Sellamuthu, Rajendran; Fisher, Alexa; Feng, Hailin; Wu, Tong; MacVittie, Thomas J.; Orschell, Christie M.
<x xml:space="preserve">Abstract</x> Abstract Manipulations of lethally-irradiated animals, such as for administration of pharmaceuticals, blood sampling, or other laboratory procedures, have the potential to induce stress effects that may negatively affect morbidity and mortality. To investigate this in a murine model of the hematopoietic acute radiation syndrome, 20 individual survival efficacy studies were grouped based on the severity of the administration (Admn) schedules of their medical countermeasure (MCM) into Admn 1 (no injections), Admn 2 (1–3 injections), or Admn 3 (29 injections or 6–9 oral gavages). Radiation doses ranged from LD30/30 to LD95/30. Thirty-day survival of vehicle controls in each group was used to construct radiation dose lethality response relationship (DRR) probit plots, which were compared statistically to the original DRR from which all LDXX/30 for the studies were obtained. The slope of the Admn 3 probit was found to be significantly steeper (5.190) than that of the original DRR (2.842) or Admn 2 (2.009), which were not significantly different. The LD50/30 for Admn 3 (8.43 Gy) was less than that of the original DRR (8.53 Gy, p < 0.050), whereas the LD50/30 of other groups were similar. Kaplan-Meier survival curves showed significantly worse survival of Admn 3 mice compared to the three other groups (p = 0.007). Taken together, these results show that stressful administration schedules of MCM can negatively impact survival and that dosing regimens should be considered when constructing DRR to use in survival studies.